"We Do Not Look At Them As They Really Are": Technics and Photogénie in Jean Epstein's Film-Philosophy. Issue 3 (October 2018) - Sullivan, Gordon
Abstract : This article argues that we can understand Jean Epstein's theory of photogénie as an instance of technics. Starting from a reading of Epstein's final fictional film Le Tempestaire (1947), we can see that Epstein collapses the distinction between human and technological. This insight leads to a discussion of Epstein's theory of photogénie more generally, and one that highlights the term's relationship to temporality. This temporal dimension recalls Bernard Stiegler's discussion of technics in Technics and Time (3 volumes). As the series evolves, Stiegler increasingly foregrounds cinema as technics, and the essay ends with a discussion of the ways that Epstein's understanding of photogénie can press on Stiegler's claims.